Experience of Audit Committee Members and Audit Quality - Sultana, Nigar; Singh, Harj; Rahman, A. (Routledge Journals, 2019)
We investigate whether the experience of audit committee members is associated with audit quality. In order to comprehensively analyse the experience of audit committee members, we include audit committee member tenure, age and multiple-directorships in our analysis. Using observations from 2001 to 2012, we undertake analysis on 13,155 firm-year observations and find that all our proxies of audit committee member experience are positively associated with audit fees. A range of additional tests, including using discretionary accruals as an alternative measure of audit quality and differences-in-differences analysis, support our main findings and our results consequently make a number of contributions to both the literature and policy making. One possible policy contribution is that regulators may wish to consider audit committee characteristics representing experience when framing recommendations to improve audit quality and thereby, financial reporting by firms.